2014
DOI: 10.1063/1.4893698
|View full text |Cite
|
Sign up to set email alerts
|

On the charge transfer between single-walled carbon nanotubes and graphene

Abstract: It is important to understand the electronic interaction between single-walled carbon nanotubes (SWNTs) and graphene in order to use them efficiently in multifunctional hybrid devices. Here we deposited SWNT bundles on graphene-covered copper and SiO 2 substrates by chemical vapor deposition and investigated the charge transfer between them by Raman spectroscopy. Our results revealed that, on both copper and SiO 2 substrates, graphene donates electrons to the SWNTs, resulting in p-type doped graphene and n-typ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…cm −1 , respectively (Liu et al, 2017), as shown in Figure 4B. The downshift of several wavenumbers indicates electron transfer from Fe 3 O 4 nanospheres to 3D RGO, as illustrated in the literature (Rao et al, 2014;Hu et al, 2018b). This also confirms the formation of heterostructures between RGO and Fe 3 O 4 in Fe 3 O 4 @RGO.…”
Section: Microstructure Characterizationssupporting
confidence: 75%
“…cm −1 , respectively (Liu et al, 2017), as shown in Figure 4B. The downshift of several wavenumbers indicates electron transfer from Fe 3 O 4 nanospheres to 3D RGO, as illustrated in the literature (Rao et al, 2014;Hu et al, 2018b). This also confirms the formation of heterostructures between RGO and Fe 3 O 4 in Fe 3 O 4 @RGO.…”
Section: Microstructure Characterizationssupporting
confidence: 75%
“…Upon contact with semiconducting CNTs, the G‐peak of graphene is positively shifted by ≈10 cm −1 , implying p‐type doping of the graphene. Doping of graphene would be caused by hole transfer from CNTs to graphene …”
Section: Resultsmentioning
confidence: 99%
“…The scanning electron microscope (SEM) image in Figure 3a presents the boundary between the PET substrate and the graphene electrode of the fabricated sensor, which indicates that the graphene is clearly defined, and the CNTs are uniformly dispersed over the entire area without aggregation. [34] Figure 4a shows an optical image of the fabricated UV sensor, which demonstrates that all components of the device are fully transparent. We also measured the Raman spectra of CNT, graphene, and a CNT-graphene hybrid with 532 nm laser excitation.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%
“…Variations in the electronic structure of SWNTs have previously been reported when in contact with graphene nanoribbons. 20 A few experimental studies have [21][22][23] addressed the shis in the Raman mode frequencies of SWNTs and SLG in the hybrid system and it was claimed that the shis occur as a consequence of charge transfer between the two at the heterojunction. In these studies, the charge transfer between SWNTs and SLG, responsible for the Raman peak shis, is ascribed to the work-function difference between these structures and any other atomic interaction between the two components is not taken into account.…”
Section: Introductionmentioning
confidence: 99%